Biomedical applications of silkworm (Bombyx Mori) proteins in regenerative medicine (a narrative review). (7th December 2021) - Khosropanah, Mohammad Hossein; Vaghasloo, Mahdi Alizadeh; Shakibaei, Mehdi; Mueller, Anna‐Lena; Kajbafzadeh, Abdol‐Mohammad; Amani, Leila; Haririan, Ismaeil; Azimzadeh, Ashkan; Hassannejad, Zahra; Zolbin, Masoumeh Majidi
Abstract: Silk worm ( Bombyx Mori ) protein, have been considered as potential materials for a variety of advanced engineering and biomedical applications for decades. Recently, silkworm silk has gained significant importance in research attention mainly because of its remarkable and exceptional mechanical properties. Silk has already been shown to have unique interactions with cells in tissues through bio‐recognition units. The natural silk contains fibroin and sericin and has been used in various tissues of the human body (skin, bone, nerve, and so on). Besides, silk also still has anti‐cancer, anti‐tyrosinase, anti‐coagulant, anti‐oxidant, anti‐bacterial, and anti‐diabetic properties. This article is supposed to describe the diverse biomedical capabilities of B. Mori silk as the appropriate biomaterial among the assorted natural and artificial polymers that are presently accessible, and ideal for usage in regenerative medicine fields.